2021
DOI: 10.1186/s40510-021-00363-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of orthodontic treatment experiences during COVID-19: a cross-sectional study

Abstract: Background COVID-19 has impacted the care of patients undergoing orthodontic treatment. We aimed to provide an overall view of patients’ perspectives, concerns, and expectations towards their treatment throughout the clinic lockdown during the pandemic; and to assess patients’ levels of mental distress and its association with their confidence in resuming care. Methods An anonymous, validated, in-person paper questionnaire was distributed to adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 46 publications
1
28
0
3
Order By: Relevance
“…The overall risk of bias assessment of the included studies is presented in Tables S1 and S2 in Supplementary Materials. Five studies reported a moderate level of bias [21][22][23][24][25], while the remaining five studies showed low quality [26][27][28][29][30].…”
Section: Risk Of Biasmentioning
confidence: 98%
See 4 more Smart Citations
“…The overall risk of bias assessment of the included studies is presented in Tables S1 and S2 in Supplementary Materials. Five studies reported a moderate level of bias [21][22][23][24][25], while the remaining five studies showed low quality [26][27][28][29][30].…”
Section: Risk Of Biasmentioning
confidence: 98%
“…In surveys administered through online platforms (Table S1 in Supplementary Materials), all studies reported the survey design describing the target population or sample frame. For IRB approval and informed consent process, IRB approval was obtained by seven out of eight studies [21][22][23][24]26,29,30], informed consent was obtained by four studies [22,25,28,29], and data protection was reported by only one study [22], while it was not applicable by four surveys [21,23,27,29]. Development and pre-testing were performed by only two studies [22,30].…”
Section: Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations